Development of a single-cell atlas for woodland strawberry (Fragaria vesca) leaves during early Botrytis cinerea infection using single-cell RNA-seq. Issue 1 (19th January 2022) - Bai, Yibo; Liu, Hui; Lyu, Haimeng; Su, Liyao; Xiong, Jinsong; Cheng, Zong-Ming (Max)
Abstract: Pathogen invasion leads to fast, local-to-systemic signal transduction that initiates plant defense responses. Despite tremendous progress in past decades, aspects of this process remain unknown, such as which cell types respond first and how signals are transferred among cell types. Here, we used single-cell RNA-seq of >50 000 single cells to document the gene expression landscape in leaves of woodland strawberry during infection by Botrytis cinerea and identify major cell types. We constructed a single-cell atlas and characterized the distinct gene expression patterns of hydathode, epidermal, and mesophyll cells during the incubation period of B. cinerea infection. Pseudotime trajectory analysis revealed signals of the transition from normal functioning to defense response in epidermal and mesophyll cells upon B. cinerea infection. Genes related to disease resistance showed different expression patterns among cell types: disease resistance-related genes and genes encoding transcription factors were highly expressed in individual cell types and interacted to trigger plant systemic immunity to B. cinerea . This is the first report to document the single-cell transcriptional landscape of the plant pathogenic invasion process; it provides new insights into the holistic dynamics of host–pathogen interactions and can guide the identification of genes and the formulation of strategies for resistant cultivar development.